Genome Editing Targets for Improving Nutrient Use Efficiency and Nutrient Stress Adaptation - Sathee, Lekshmy; Jagadhesan, B.; Pandesha, Pratheek H.; Barman, Dipankar; Adavi B, Sandeep; Nagar, Shivani; Krishna, G. K.; Tripathi, Shailesh; Jha, Shailendra K.; Chinnusamy, Viswanathan (Frontiers in Genetics, 2022)
In recent years, the development of RNA-guided genome editing (CRISPR-Cas9 technology) has revolutionized plant genome editing. This review outlines potential targets suitable for genome editing for understanding and improving nutrient use efficiency and nutrient stress tolerance. The specific genome editing targets for improving nutrient response and nutrient stress tolerance is compiled. The development of stress-resistant plants through CRISPR-Cas technology is expected to enhance the pace of genetic improvement for nutrient stress tolerance of crops and improve the sustainability of agriculture. Under nutrient deficiency conditions, different transcription factors and regulatory gene networks work together to maintain nutrient homeostasis. Transcription factors such as LBDs SPL9, calcium signaling kinase CIPK23 are negative regulators of nitrogen (N) deficiency response, potential negative regulators of phosphorus (P) signalling are AtIPS1/2, AtPHO2, AtWRKY6, AtWRKY43, miR827. The E3 ubiquitin ligases HRZs/BTS, are negative regulators of iron deficiency responses. RECEPTOR FOR ACTIVATED C KINASE 1 (RACK 1) a WD40-repeat family protein is a a potent negative regulator of ABA-mediated stress signalling. The FARNESYLTRANSFERASE A (FTA) and ENHANCED RESPONSE TO ABA1 (ERA1), which encodes subunits of the protein farnesyltransferase enzymes negatively regulate ABA and brassinosteroid signaling in Arabidopsis thaliana. The negative regulators are potential targets for genome editing for down-regulation, up-regulation, or knock-out, that may positively affect nutrient uptake and stress signalling under resource poor conditions.